Quality of Working Life in Chonprathan Medical Centre, Srinakharinwirot University - โพธิสกุล เปมิกา; โพธิสกุล เปมิกา; สุนทรวิภาต ลลิตา นิพิฐประศาสน์ (Thai Interdisciplinary and Sustainability Review, 2019)
The objectives of this research were to study the quality of working life of nurses in Chonphathan Medical Centre, Srinakharinwirot University, and the relationship between the personal, nature of work, and organisation’s environment factors and the quality of work life of nurses, using samples of 161 nurses in Chonprathan Hospital, Srinakharinwirot University. Questionnaires were used in data collection and statistical methods used for data analysis were percentage, mean, standard deviation, Pearson’s product-moment correlation coefficient and multiple regression analysis at the .05 level of significance. The research results showed that the opinions of the nurses on quality of work life were at moderate level; whereas the opinions on job characteristics and organisational climate were at high levels. Hypothesis testing revealed that job characteristics, importance of work, work autonomy, work feedback, work standard, increasing work values, and organisational climate were positively correlated to the quality of working life of the nurses. Moreover, the factors of organisational climate could alter the quality of work life of the nurses up to 77.90 percent.